Effect of file sizes on encryption and decryption in constrained devices / Nurnadia Sapri - Sapri, Nurnadia (2015)
TCP protocol can be used in the transmission of data from one host to another host. Simply, it is unsecure because the attacker can break security parameters to obtain access to the data that currently being sent. As a communication and transmission of files over Internet has increased exponentially since last few years, there is need of security in such file transfer. Therefore, the effect of file sizes on encryption and decryption in constrained devices have been analyzed using two types of cryptographic algorithm which is AES-128 (symmetric-key encryption) and RSA- 2048 (asymmetric-key encryption) based on the different file size, execution time, and the throughput. AES-128 has faster encryption and decryption time, low power consumption, faster in hardware and software implementation, and high throughput compared to RSA-2048. Moreover, AES-128 algorithm provides higher security compared to RSA-2048. Therefore, AES-128 gives higher confidentiality compared to RSA-2048 and it will be most suitable encryption algorithm to be implemented in the TCP protocol.